Disturbance: a double‐edged sword for restoration in a changing climate. Issue 1 (12th April 2022) - Brambila, Alejandro; Reed, Paul B.; Bridgham, Scott D.; Roy, Bitty A.; Johnson, Bart R.; Pfeifer‐Meister, Laurel; Hallett, Lauren M.
Abstract : Ecological restoration often relies on disturbance as a tool for establishing target plant communities, but disturbance can be a double‐edged sword, at times initiating invasion and unintended outcomes. Here we test how fire disturbance, designed to enhance restoration seeding success, combines with climate and initial vegetation conditions to shift perennial versus annual grass dominance and overall community diversity in Pacific Northwest grasslands. We seeded both native and introduced perennial grasses and native forbs in paired, replicated burned‐unburned plots in three sites along a latitudinal climate gradient from southern Oregon to central‐western Washington. Past restoration and climate manipulations at each site had increased the variation of starting conditions between plots. Burning promoted the expansion of extant forbs and perennial grasses across all sites. Burning also enhanced the seeding success of native perennial grass and native forbs at the northern and central site, and the success of introduced perennial grasses across all three sites. Annual grass dominance was driven more by latitude than burning, with annuals maintaining their dominance in the south and perennials in the north. At the same time, unrestored grasslands surrounding all sites remained dominated by perennial grasses, suggesting that initial plot clearing may have allowed for annual grass invasion in the southern site. When paired with disturbance, further warming may increase the risk of annual grass dominance, a potentially persistent state.